Pengaruh Pemberian Jus Wortel pada Penderita Hipertensi di Posyandu Lansia Desa Montong Kabupaten Tuban - Dita Marta Sari; Dwi Kurnia PS; Ahmad David Royyifi Arifin (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hypertension is a medical condition characterized by systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg, which are at risk of causing various complications. One of the efforts to control hypertension is through non-pharmacological therapies such as a healthy diet, including the consumption of carrot juice. This study aims to determine the difference in blood pressure reduction in elderly people with hypertension who are given carrot juice at the Posyandu Elderly in Montong Village, Tuban Regency. The study uses a quantitative approach with an experimental quasy design and a